Community participation in the management of palm leaf manuscripts as Lanna cultural material in Thailand - Piyapat Jarusawat (2018)
© 2018, Emerald Publishing Limited. Purpose: The cultural heritage of the Lanna region of upper Northern Thailand is unique. One of its distinctive features is palm leaf manuscripts (PLMs), which are viewed simultaneously as examples of sacred writing and religious symbols, means of transferring cultural knowledge, artefacts of beauty and fragile historical documents. Local people still care about these objects, and speak the language but knowledge of the script is limited. The purpose of this paper is to explore the views of community members and experts about the value and management of PLMs as the basis for developing a model of community-based collection management. Design/methodology/approach: Because the purpose was to explore differing perceptions and beliefs around PLMs the study adopted an interpretivist worldview. Data were collected through interviews with local people with an interest in PLMs and experts who advised on organising them. In addition, observation and a photo inventory method was used to collect data. Data were analysed thematically. Findings: The results showed that while both groups saw the value of the knowledge PLMs contained, the community placed particular importance on the earning of “merit” through activities related to them as Buddhist objects. Experts gave particular emphasis to the knowledge of herbal medicine contained in the PLMs. The community valued indigenous storage and preservation practices. Experts were particularly pre-occupied with the intellectual property issue around medical knowledge and convenient storage and digitisation. Research limitations/implications: Existing theory around libraries, archives and museums suggest some starting points for how community participation might be managed, but the unique circumstances of Lanna PLMs calls for a distinctive approach. Practical implications: The paper identifies a pathway suitable to the Lanna context that can build on current local practices, to enhance community participation in the management of PLMs, including a consideration of the role of information professionals. Originality/value: This paper is one of the first to extend thinking about participatory practices in the library, archive and museum literature to the context of Thailand and specifically to the case of PLMs, in the Lanna region. Rigorous data analysis of a substantial body of evidence has enhanced the understanding of the different types of value placed on PLMs. It identifies an important but not unbridgeable tension between how local people and experts view PLMs. It builds on previous library, archive and museum theory to propose a realistic model of how communities and experts (including librarians) can work together to protect the rich cultural resource represented by PLMs.